(Ir)resistible Stairs: Public Health, Desiring Practices, and Material-Symbolic Ableism. Issue 1 (2nd January 2022) - Hamraie, Aimi
Abstract : Irresistible staircases are material symbols for the "new public health." Popularized by sustainability standards and health-centered approaches to architecture and urbanism, they intend to motivate health-centered behaviors. This paper uses critical disability theory to analyze built forms, visual and textual narratives, and works of art, showing that the irresistible staircase aims to both produce desires for health and quell resistance. It traces irresistible staircases as they appear in Nashville, Tennessee, a city with a dedicated public health urban plan. Then, it considers the broader context of resistance to stairs by disability activists, who propose alternative desiring practices.